Multifunctional multilevel moisture sensor (Nexo Revista Científica, 2022)
Controlling the moisture level is especially important when irrigating various crops to obtain a resistant, stable harvest and save water resources. Over moistening of the soil adversely affects the soil structure and can lead to salinization, waterlogging, and acidification. In addition, the formation of surface water runoff from the fields causes depletion of nutrients, oxygen starvation, and, ultimately, soil degradation. The degradation of fields (areas of the field) leads to the withdrawal of the field from crop rotation (exploitation), a reduction in acreage, the need for agrotechnical measures, reclamation, and, as a result, high financial costs. Currently applied irrigation technologies lead to the withdrawal of up to 50% of irrigated land. Therefore, the technology of differentiated irrigation with constant control over the condition of the soil and plants will help eliminate these negative consequences while increasing the yield and reducing the consumption of water, electricity, and labor costs. For the implementation of this technology, sensors are needed to control the moisture and temperature of the soil at different depths and perform operational control of the water supply to the field. The implementation of a constant connection between the field and the plant with the water supply system will allow creating digital irrigation map and forming of a database about the irrigated field underlying the information and created advisory system. The system for the continuous monitoring of soil moisture and temperature at different depths is based on IT technology with data transmission via radio communication channels. It uses platforms for data transmission via such communication channels as LoRaWAN (highly economical wireless communication interface from ICBCom), GSM (Groupe Spécial Mobile - the global standard for digital mobile cellular communication), and the Internet.